PENGARUH KETERAMPILAN KERJA TERHADAP KINERJA PENGURUS KOPERASI WANITA PADANG TERUBUK PEKANBARU - Jamilah '; Gimin '; Fenny Trisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The socio-economic development and cooperation development alone will require the cooperative to be able to increase the role and function if it does not want to match with other businesses. Therefore, one way to be able to maintain the existence of the cooperative is to improve the performance of cooperative management. One of the factors that affect the performance of the board is the personal factor. The personal factors includes: knowledge, skills, confidence, motivation and commitment of the individual. Board was given the mandate by the members for manage the cooperative to reach the objectives it has set. They are responsible for the actions and efforts for the interests and benefits of cooperative in accordance with the decision the “Meeting Members”. With it, the cooperative board has the capacity and skills demanded adequate employment. One of the facts found in the Women's Cooperative Padang Terubuk Pekanbaru is the number of cooperative members fluctuated, the low interest of members to attend a meeting of members held each month and the annual meeting of the cooperative. In interviews for this research, many members of the cooperative who revealed that the explanation of the board members' meeting is often difficult to understand. The purpose of this research was to determine the effect on performance management skills Women's Cooperative in Padang Terubuk Pekanbaru. In a test of t is known that t (6.448)> t table (2.024) and Sig. (0,000) <0.05. it means that, work skills variables significantly influence the performance of the board. Then, on the test R squre known value of R square of 0.522. The meaning that the contribution of occupational skills influence on the performance of the board is 52.2% and 47.8% for influenced by other variables is not included in this regression model.Keywords: skill of work, Performance Management